CRUSTAL VERSUS ASTHENOSPHERIC ORIGIN OF RELIEF OF THE ATLAS MOUNTAINS OF MOROCCO - Missenard Y.; de Lamotte D.F.; Leturmy P.; Zeyen H.; Petit C.; Sébrier M.; Saddiqi O. (My University, 2006)
We investigate the respective roles of crustal tectonic shortening and asthenospheric processes on the topography of the High Atlas and surrounding areas (Morocco). The lithospheric structure is modeled with a direct trial-and-error algorithm taking into account gravity (Bouguer and free air), geoid, heat flow, and topography. Three parallel cross sections, crossing the High Atlas and Anti-Atlas ranges, show that the lithosphere is thinned to 60 km below these mountain ranges. An analysis of the effect of the lithospheric thinning allows us to conclude that the whole topography of the Anti-Atlas, which belongs to the Sahara domain, is due to asthenospheric processes. In the High Atlas the lithospheric thinning explains a third of the relief of the western High Atlas, 500 m for a mean altitude of 1500 m, and half of the relief of the central High Atlas, 1000 m for a mean altitude of 2000 m. At the scale of Morocco the domain affected by lithospheric thinning forms an elongated NE-SW strip crossing not only the main structural zones but also the Atlantic margin to the south and the Africa-Eurasia plate boundary to the north. This major lithospheric thinning is associated with Miocene to recent alkaline volcanism and seismicity. We propose that this thermal anomaly is related to a shallow mantle plume, emplaced during middle to late Miocene time, during a period of relative tectonic quiescence. Copyright 2006 by the American Geophysical Union.
Keywords: Miocene; Cenozoic::Neogene::Miocene; Кайнозой::Неоген::Миоцен